Models of cuspy triaxial stellar systems. IV : rotating systems - Carpintero, Daniel Diego (2016)
We built two self--consistent models of triaxial, cuspy, rotating stellar systemsadding rotation to non-rotating models presented in previous papers of thisseries. The final angular velocity of the material is not constant and varies withthe distance to the center and with the height over the equator of the systems,but the figure rotation is very uniform in both cases. Even though the additionof rotation to the models modifies their original semiaxes ratios, the finalrotating models are considerably flattened and triaxial. An analysis of theorbital content of the models shows that about two thirds of their orbits arechaotic but, nevertheless, the models are very stable over intervals of the orderof one Hubble time. The bulk of the regular orbits are short axis tubes, whilelong axis tubes are replaced by tubes whose axes lie on the short--long axesplane, but do not coincide with the major axis. Other types of regular orbitsthat do not appear in non--rotating systems, like horseshoes and orbits thatcross themselves, are also found in the present models. Finally, ourfrequency maps show empty regions where studies of orbits on fixed potentialsfound orbits, a likely consequence of the self--consistency of our models thatexcludes them.